2020
DOI: 10.1002/asi.24369
|View full text |Cite
|
Sign up to set email alerts
|

“To protect my health or to protect my health privacy?” A mixed‐methods investigation of the privacy paradox

Abstract: This paper examines the role of privacy in the health context by investigating the influence of privacy concerns and perceived benefits on individuals' acceptance of health technologies used by healthcare providers and their own adoption of mobile health technologies. The study adopts a two‐stage sequential mixed‐methods design. The first stage is a quantitative survey of 447 citizens from two countries. The second stage involves 50 qualitative interviews which further untangle the roles of privacy concern and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 41 publications
0
31
1
Order By: Relevance
“…Contact tracing applications may be described as both health applications and location‐based services (LBS) applications. In both these contexts, extant literature provides preliminary support for the importance of perceived benefits on acceptance of health systems and mobile health applications (Angst & Agarwal, 2009; Fox, 2020; Redmiles, 2020), and perceived usefulness on continued use of LBS apps (Zhou, 2013). Privacy concerns have been negatively associated with individuals' acceptance of health systems (Fox & James, 2020) and willingness to disclose personal information to health websites and online communities (Bansal et al, 2010; Kordzadeh & Warren, 2017), whereas privacy risks have been negatively linked to individuals' continued use of LBS apps (Zhou, 2013), and willingness to disclose the location to these apps (Sun et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Contact tracing applications may be described as both health applications and location‐based services (LBS) applications. In both these contexts, extant literature provides preliminary support for the importance of perceived benefits on acceptance of health systems and mobile health applications (Angst & Agarwal, 2009; Fox, 2020; Redmiles, 2020), and perceived usefulness on continued use of LBS apps (Zhou, 2013). Privacy concerns have been negatively associated with individuals' acceptance of health systems (Fox & James, 2020) and willingness to disclose personal information to health websites and online communities (Bansal et al, 2010; Kordzadeh & Warren, 2017), whereas privacy risks have been negatively linked to individuals' continued use of LBS apps (Zhou, 2013), and willingness to disclose the location to these apps (Sun et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…They found that perceived benefits are a strong motivator in sharing private information. Likewise, Fox [ 33 ] investigated the influence of privacy calculus variables on individuals’ intention to adopt mobile health technologies. The paper finds a stronger influence of benefits compared to risks and concerns.…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare is information-intensive, since many activities are enabled through storing, processing, and analyzing data. An EHR increases efficiency in healthcare delivery, simplifies monitoring patient health, facilitates monetary savings, reduces paper-based errors, and improves diagnoses and treatments [ 2 , 3 , 4 , 5 , 6 ]. Governments and healthcare systems promote national patient health records as “a way of preserving patients’ health and medical information and maintaining their data in a central facility that ideally can be shared between different healthcare providers” ([ 7 ], p. 1).…”
Section: Introductionmentioning
confidence: 99%